Physiological Ocular Changes in Various Trimesters of Pregnancy - Agrawal, Nisha; Agarwal, Lalit T; Lavaju, Poonam; Chaudhary, Sanjib Kumar (Nepalese Journal of Ophthalmology, 2018)
Introduction: A large number of hormonal, metabolic, immunologic and haematological changes occur in all organ system of female body during pregnancy. Human eye and its function are no exception to these changes. Purpose: To evaluate physiological ocular changes in various trimesters of pregnancy and to compare them amongst the three trimesters. Patients and Methods: A hospital based cross sectional study, using judgmental convenient sampling method, was done in both eyes of 120 pregnant females (40 in each trimester), with known last menstrual period, attending antenatal clinic of BPKIHS, Dharan. Women with known systemic or ocular diseases like conjunctivitis, keratitis, iridocyclitis, glaucoma, refractive error, were excluded. Demographic details of all patients were recorded and detailed ocular examination, including best corrected visual acuity, slit lamp examination, vertical and horizontal keratometry, central corneal thickness and intraocular pressure were performed and recorded. A comparison of these parameters was made amongst three trimesters. Results: Visual acuity of all the subjects was 0 logMAR. Corneal curvature, both vertical and horizontal, significantly increased towards third trimester. Central corneal thickness progressively increased from first to third trimester (p= 0.019 Right eye, 0.016 Left eye). In contrary to this, intraocular pressure significantly decreased during successive stages of pregnancy (P=0.000 both eye). Conclusion: Significant increase in corneal curvature and central corneal thickness along with, decrease in intraocular pressure occur during successive trimesters of pregnancy. All pregnant women should have routine ocular examination; changes noted, if any, should receive attention and period of gestation should be considered prior to making a diagnosis.